(untitled) (Nexus International Journal of Science and Education, 2024)
This study aimed to help reading teachers handle individualized reading intervention programs for struggling readers beset with problematic situations that, when not properly understood, can bring detriment to the reading progress of children with specific reading difficulties. This phenomenological inquiry on the lived experiences of reading teachers handling face-to-face, one-on-one reading instruction for struggling readers was conducted with 10 elementary reading teachers to explore their experiences towards giving individualized intervention. This study revealed that reading teachers handling individualized instruction face the following challenges: low motivation and engagement, lack of professional development, and less parental involvement; while coping mechanisms they adopted, namely, the reading teachers exhibited patience and empathy, used differentiation in reading instruction, and incorporated technology in handling individualized reading interventions for struggling readers. Among the educational insights that the participant underscored include individual differences deemed crucial, early intervention as indispensable, and parental and community involvement as necessary in successfully implementing the individualized reading intervention for struggling readers. Implications drawn from the study's conclusions include institutionalizing capacity-building programs to empower reading teachers and seeking assistance from the community and stakeholders for schools to implement reading programs and augment readers’ progress fully.